Impact of Oral versus Intravenous Ibuprofen on Neurodevelopmental Outcome: A Randomized Controlled Parallel Study - Eras, Zeynep; Gokmen, Tulin; Erdeve, Omer; Ozyurt, Banu Mutlu; Saridas, Bagdagul; Dilmen, Ugur (American Journal of Perinatology, 2013)
Objective Although neurodevelopmental outcomes related to the management of patent ductus arteriosus with intravenous indomethacin and ibuprofen are known, little data on the long-term effects of oral ibuprofen can be found in the literature.Method A follow-up study of 99 infants with birth weight ≤ 1,500 g and gestational age ≤ 32 weeks who received either oral or intravenous ibuprofen for patent ductus arteriosus was conducted to assess at 18 to 24 months (corrected age), abnormal neurological, neurosensory, and cognitive impairment were defined as follows:neurological outcomes included moderate/severe cerebral palsy, neurosensory outcomes included bilateral hearing loss and blindness in either eye, and cognitive impairment included mental developmental index score < 70.Results The 18- to 24-month (corrected age) long-term outcomes of 30 subjects who received oral ibuprofen were compared with 27 subjects who received intravenous ibuprofen by certified and experienced examiners who were blind to the definitions of the groups. The results revealed that the long-term outcomes of the treatment regimens did not significantly differ.Conclusions Preterm infants who were treated with oral ibuprofen for patent ductus arteriosus had similar neurological, neurosensory, and cognitive outcomes to patients who received intravenous ibuprofen at 2 years of age.
Keywords: ibuprofen; long-term outcome; neurodevelopmental outcome; preterm; very low birth weight